How to promote descriptions in dynamic charts in light of transparency? A study on the accessibility barriers faced by citizens with severe visual impairment - Marques, João Marcelo Dos Santos; Ferreira, Simone Bacellar Leal (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: With the advent of digital transformation, government agencies provide Information Systems (IS) with data visualizations, including dynamic graphs. However, people with severe visual impairment still face barriers on the Web when it comes to accessing the information presented in these graphics. Problem: This part of society cannot understand the information described in these visual contents, meaning they cannot graphically construct a mental model. Solution: Recommendations for improvements grouped into four categories covering familiarity with the use of keys, web content, understanding of information, preference for descriptions encoded in two categories (captions and values; color), navigation features, ways of acquiring descriptions, dissemination of information. SI Theory: This article was conceived under the umbrella of Software Systems Theory. Method: This work is empirical in nature with a qualitative methodological approach, in which direct observation and various research strategies, techniques and analysis of results were used. Summary Results: Based on a web survey with 41 participants and a subsequent field study with the participation of 12 people with visual impairments, the demands and preferences of these citizens were determined, based on tests carried out on portals at three government levels (municipal, state and federal) and semi-structured interviews. Contributions to SI: As a contribution, this article can assist research in Information Systems aiming at describing dynamic graphics from the perspective of information transparency for the understanding of citizens with visual impairments, in addition to promoting research in HCI and related areas aligned with GranDSI-BR 2016-2026.